2005
DOI: 10.1210/jc.2005-0404
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Common Polymorphisms in Candidate Genes for Insulin Resistance and Obesity on Weight Loss of Morbidly Obese Subjects after Laparoscopic Adjustable Gastric Banding and Hypocaloric Diet

Abstract: These data demonstrate that genetic factors, which play an important role in the regulation of body weight, may account for differences in the therapeutic response to LAGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
3

Year Published

2008
2008
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 38 publications
2
35
0
3
Order By: Relevance
“…ECW (l) did not change but the increase of ECW/ICW ratio was statistically significant. Moreover, we observed that a significant proportion of patients (15%) had a relatively modest weight loss, similar to previous reported data, 21 and 5% of patients did not lose weight ( Figure 2). A comparable variability in body composition changes after LAGB was also a characteristic of our study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…ECW (l) did not change but the increase of ECW/ICW ratio was statistically significant. Moreover, we observed that a significant proportion of patients (15%) had a relatively modest weight loss, similar to previous reported data, 21 and 5% of patients did not lose weight ( Figure 2). A comparable variability in body composition changes after LAGB was also a characteristic of our study.…”
Section: Discussionsupporting
confidence: 92%
“…To date, the relationship between À174G4C IL6 polymorphism and obesity has been investigated by several comparably small studies with inconsistent results. [16][17][18]21,[46][47][48] 54,55 Our data contribute to defining the C(À) carriers as risk subjects because, although they have a lower FM (%) and trunk FM (%), and higher LM (kg), ratio LM/FM, BCM (kg) and RMR, they show a significantly higher risk for cardiovascular diseases at baseline. With regard to fluid distribution, C(À) carriers showed a higher content of TBW (l) and ECW/ICW ratio than C( þ ) carriers.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Patients homozygous for the C allele had increases in IL-6 levels post-surgery, whereas G carriers had decreases. In an alternate study of weight loss following gastric banding surgery, homozygous carriers of the G allele lost significantly more weight than GC or CC subjects (Sesti et al, 2005). This suggests that GG carriers may respond more favorably to gastric surgery interventions (that is, better decreases in both body weight and inflammation).…”
Section: Diet-gene Interactions and Adipokines C Stryjecki And Dm Mutchmentioning
confidence: 99%